Design of two alternative routes for the synthesis of naftifine and analogues as potential antifungal agents - Abonia, Rodrigo (2018)
Two practical and efficient approaches have been implemented as alternative procedures for the synthesis of naftifine and novel diversely substituted analogues 16 and 20 in good to excellent yields, mediated by Mannich-type reactions as the key step of the processes. In these approaches, theγ-aminoalcohols 15 and 19 were obtained as the key intermediates and their subsequent dehydration catalyzed either by Brønsted acids like H2SO4 and HCl or Lewis acid like AlCl3, respectively, led to naftifine, along with the target allylamines 16 and 20. The antifungal assay results showed that intermediates 18 (bearing both a β-aminoketo- and N-methyl functionalities in their structures) and products 20 were the most active. Particularly, structures 18b, 18c, and the allylamine 20c showed the lowest MIC values, in the 0.5-7.8 μg/mL range, against the dermatophytes Trichophyton rubrum and Trichophyton mentagrophytes. Interesting enough, compound 18b bearing a 4-Br as the substituent of the phenyl ring, also displayed high activity against Candida albicans and Cryptococcus neoformans with MIC80 = 7.8 μg/mL, being fungicide rather than fungistatic with a relevant MFC value = 15.6 μg/mL against C. neoformans.